2006
DOI: 10.1128/aem.00809-06
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiles and Genetic Diversity of Denitrifying Communities in Activated Sludge after Addition of Methanol or Ethanol

Abstract: External carbon sources can enhance denitrification rates and thus improve nitrogen removal in wastewater treatment plants. The effects of adding methanol and ethanol on the genetic and metabolic diversity of denitrifying communities in activated sludge were compared using a pilot-scale plant with two parallel lines. A full-scale plant receiving the same municipal wastewater, but without external carbon source addition, was the reference. Metabolic profiles obtained from potential denitrification rates with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 41 publications
6
54
0
1
Order By: Relevance
“…60 mg NO3 − -N g −1 [dry wt] h −1 ) under steady-state conditions. These rates are much higher than those recorded for activated sludge with various soluble substrates 13) . However, the SPD reactor-derived washed sludge showed approximately one-third lower denitrification rates with fresh PHBV as the substrate than did the reactors themselves.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…60 mg NO3 − -N g −1 [dry wt] h −1 ) under steady-state conditions. These rates are much higher than those recorded for activated sludge with various soluble substrates 13) . However, the SPD reactor-derived washed sludge showed approximately one-third lower denitrification rates with fresh PHBV as the substrate than did the reactors themselves.…”
Section: Discussionmentioning
confidence: 48%
“…In the present study, therefore, nirS and nosZ genes, encoding cytochrome cd1 nitrite reductase and nitrous oxide reductase, respectively 45) , were used as molecular markers to assess the community composition of denitrifying bacteria in the PHBV-SPD process. These denitrifying-enzyme genes as well as the Cu-containing nitrite reductase gene, nirK, have been used for the molecular characterization of denitrifying microbial communities in different environments including wastewater treatment systems 2,13,32,44,45) . In addition, the predominant culturable denitrifying bacteria from PHBV-SPD reactors were isolated, phylogenetically identified, and studied in terms of their substrate specificity.…”
mentioning
confidence: 99%
“…Some culture-independent molecular ecology techniques such as fluorescence in situ hybridization, denaturing gradient gel electrophoresis, genetic libraries, and quantitative realtime polymerase chain reaction (PCR) have been applied in a number of studies concerned with the heterotrophic denitrifying communities in wastewater treatment systems (Throbäk et al 2004;Hallin et al 2006;Warneke et al 2011). In addition, barcoded pyrosequencing method was recently used for analyzing bacterial community structural changes of these key denitrifying genes (Mao et al 2011;Zhao et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, microorganisms fed with different carbon sources showed distinct features. A report demonstrated that the metabolic profiles obtained from potential denitrification rates with 10 electron donors were altered with their preferences for certain compounds after supplementing methanol or ethanol, and that methanol had the greater impact (Hallin et al 2006).…”
Section: Removal Of Nitrate (Denitrification) and Perchloratementioning
confidence: 99%